THE EFFECT OF AN INTERACTIVE HEALTH EDUCATION ON INCREASING KNOWLEDGE ABOUT STUNTING IN ADOLESCENTS AT RURAL OF MAYANG: PENGARUH PENDIDIKAN KESEHATAN SECARA INTERAKTIF TERHADAP PENINGKATAN PENGETAHUAN TENTANG STUNTING PADA REMAJA DESA MAYANG - Maharani, Livia Putri; Wardani, Novita Putri Eka; Naili, Naila Khoirun; Yunanto, Rismawan Adi (BIMIKI (Berkala Ilmiah Mahasiswa Ilmu Keperawatan Indonesia), 2022)
Introduction: Stunting is a nutritional problem in Indonesia that needs serious treatment. The cycle of stunting in Indonesia needs to be broken with a series of programs. The youth empowerment program has the potential to be carried out as a strategic step in breaking the stunting cycle. Methods: The method used in this research is pre-experimental using a one-group pretest and posttest approach. The sample used in this study was Mayang village youth who were selected by purposive sampling technique. The instrument used was a knowledge questionnaire about stunting based on previous research. The statistical test used in data processing is the Paired T-Test. Result: Based on the test results showed that p value = 0.001 (p < 0.05) which means that interactive health education has a significant effect on knowledge about stunting in respondents. Conclusion: Health education using interactive methods has a significant effect on increasing adolescents knowledge about stunting in Mayang Village.